Vpliv ZDR-1 na sodno prakso - Robnik, Ivan (Podjetje in delo, 2013)
The article deals with changes of the current legal regulation of employment relationships brought by the new Employment Relationship Act (ZDR-1) from the perspective of their influence on the case law in individual labor disputes. De facto effect of legal changes will be apparent only after judgments in labor disputes become final. The article draws attention to those legal grounds that will have to be defined by the case law.
Keywords: delovna razmerja; delovni spor; delovno pravo; reševanje; sodna praksa